Pembuatan dan Pemanfaatan Teh Daun Alpukat (Persea Americana Mill) yang Sehat Alami Bersama Ibu-ibu PKK Desa Hutaholbung - Putri Febiola; Delfi Ramadhini; Rezki Hotmalia Siagian; Riska Yana Hsb; Rahma Dona Siregar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on the production of herbal tea made from avocado leaves (Persea americana Mill.) and explores its potential as a health-promoting beverage. Avocado leaves are known to contain various bioactive compounds, including flavonoids, tannins, and saponins, which have antioxidant, antidiabetic, and antihypertensive properties. The production process involves selecting healthy leaves, washing, drying using a low-temperature oven (50–60°C), and grinding the dried leaves into powder. The final tea product was tested organoleptically to assess its taste, aroma, and color, and phytochemically to confirm the presence of bioactive compounds. The organoleptic test results showed that the tea has an acceptable flavor and aroma, while phytochemical tests confirmed the presence of beneficial compounds. Consumption of avocado leaf tea demonstrates potential as a functional beverage that may contribute to lowering blood pressure and blood sugar levels, as well as providing a calming effect. The findings of this study are expected to serve as a reference for the development of value-added herbal products derived from local raw materials. Such products could support efforts to improve public health and encourage the diversification of functional beverages within the community, providing both health and economic benefits for local populations.